Analisis Tindak Tutur Siswa Dalam Kegiatan Diskusi Pada Pembelajaran Bahasa Indonesia Kelas X Di SMKS Texar Karawang Tahun Ajaran 2019/2020 - Intan, Harika Valentina; Suprihatin, Dewi; Pratiwi, Winieke Dinar (Jurnal Ilmiah Wahana Pendidikan, 2024)
Speech acts are an important aspect used in student discussion activities in class. Therefore, it is necessary to pay attention to the use of speech acts spoken by students so that the learning objectives can be achieved. This study aims to describe the types of speech acts of students in discussion activities in class X Indonesian language learning at SMKS Texar Karawang in the 2019/2020 academic year. Research on Analysis of Student Speech in Discussion Activities in Class X Indonesian Language Learning at SMKS Texar Karawang Academic Year 2019/2020 is a qualitative descriptive study. The subjects of this study were students of class X RPL 3 and X TKR 4 at SMKS Texar Karawang for the 2019/2020 school year in class discussion activites. The object of this research is speech acts in class discussion of class X RPL 3 and X TKR 4 students. The techniques used in collecting data are using field recording techniques and recording techniques. The data analysis technique uses three stages, namely providing data, analyzing data, and presenting the results of data analysis. The research results can be described as follows. First, there are several types of speech acts found. Based on the objective of the act from the speaker’s point of view, it is found that the speech acts of locus, illocution, and perlocution are found. Locus speech acts include the form of news, questions and orders. Illocutionary speech acts include assertive, directive, expressive, commissive and declarative illocution. The types of speech acts that predominantly emerge from the students speech are the locus of speech acts in the form of commands, questions and assertive illocution. This type of speech act stands out and is widely used by students in discussions to ask, command, inform, state, defend, argue, suggest, say thank you, say hello, offer, do something and make people interested.